Evaluation of HLA matching in unrelated hematopoietic stem cell transplantation for nonmalignant disorders - Horan, John (American Society of Hematology, 2012)
The importance of human leukocyte antigen (HLA) matching in unrelated donor transplantation for nonmalignant diseases (NMD) has yet to be defined. We analyzed data from 663 unrelated marrow and peripheral blood stem cell transplants performed from 1995 to 2007 for treatment of NMD. Transplantation from a donor mismatched at the HLA-A, -B, -C, or -DRB1, but not -DQB1 or -DPB1, loci was associated with higher mortality in multivariate analyses (P = .002). The hazard ratio for mortality for single (7/8) and double mismatched (6/8) transplants was 1.29 (0.97-1.72; P = .079) and 1.82 (1.30-2.55; P = .0004), respectively, compared with 8/8 matched transplants. HLA mismatches were not associated with acute or chronic GVHD, but were strongly associated with graft failure. After adjustment for other factors, the odds ratio for graft failure for 7/8 and 6/8 (allele and/or antigen) matched pairs compared with 8/8 matched transplants was 2.81 (1.74-4.54; P < .0001) and 2.22 (1.26-3.97; P = .006), respectively. Patients with NMD should receive transplants from allele matched (8/8) donors if possible. Unlike the case with malignancies, HLA mismatching in NMD is associated with graft failure rather than GVHD.